Investigating EMI shielding performance of recycled polypropylene (PP) composite foams with reused metal powders - Valeria Marrocco; Rossella Surace; Elisabetta Brandonisio; Ilaria Marasco; Claudia Pagano; Cinzia Tonetti; Vito Errico; Giovanna Calò; Sabina L. Campanelli; Irene Fassi (Materials & Design)
Secondary raw materials, recycled Polypropylene (PP) and metal powders retrieved after use in the Powder Bed Fusion-Laser Beam process, are used to realize composite foams for microwave absorptance through chemical foaming. Morphological characterization allowed us to estimate foams’ relative density, cell size, distribution, and circularity. The results highlighted that metal powders contributed to air cell nucleation during the process, thus influencing the final foam morphology. Then, numerical analyses were conducted on modeled PP foams to calculate Scattering (S) parameters and Shielding Effectiveness (SE), varying air cell areas, shapes, metal particle distribution, and evaluating their impacts on EM response. Based on simulation results, the S-parameters of all samples were then measured in the X-band. The calculated SE contributions, SER and SEA, showed that foams with virgin and reused metal powders behave very similarly. Finally, four samples foamed from extruded pellets were characterized morphologically and electromagnetically. The outcomes showed extruded-based foams had a slightly decreased relative density, increased air cell numbers with lower circularity, and better uniformity in the air cell distributions. Confronting SE contributions in the X-band, SEA improved by about 10%-20% compared to the mixed samples.